IMPORTANCE OF GESTATIONAL OF MOTHERS PROFILE FOR PROPER APPLICATION OF PHYSICAL THERAPY IN OBSTETRICS (Fiep Bulletin - online, 2011)
This study aimed to characterize the profile of gestational mothers of Viçosa - MG, in order to justify the need for Physiotherapy in Obstetrics. The sample consisted of fifty women postpartum or late first calf, with an average age of twenty-two years who attended the San Sebastian Hospital, Health Post and Post Vaccination of Viçosa, MG. For its realization, we applied only once, three questionnaires: Topography and intensity Pain Questionnaire, Physical Activity and Work Questionnaire for Identifying and Gestational Disorders. The characteristic were presented with 58% urinary incontinence, urinary tract infection 29%, dyspnea 36%, 12% with varicose veins, edema at 64%, 32% constipation, hemorrhoids with 6%, 38% pain with numbness and 73% sedentary 74% and 52% worked during pregnancy. From the data collected, we can conclude that is indicated and necessary to minimize Physiotherapy in Obstetrics and / or prevent disorders of pregnancy, improving the quality of life for pregnant and postpartum women.
Keywords: postpartum; Profile Gestational; physiotherapy in obstetrics